Roadmap on emerging concepts in the physical biology of bacterial biofilms: from surface sensing to community formation. (23rd June 2021) - Wong, Gerard C L; Antani, Jyot D; Lele, Pushkar P; Chen, Jing; Nan, Beiyan; Kühn, Marco J; Persat, Alexandre; Bru, Jean-Louis; Høyland-Kroghsbo, Nina Molin; Siryaporn, Albert; Conrad, Jacinta C; Carrara, Francesco; et al.
Abstract: Bacterial biofilms are communities of bacteria that exist as aggregates that can adhere to surfaces or be free-standing. This complex, social mode of cellular organization is fundamental to the physiology of microbes and often exhibits surprising behavior. Bacterial biofilms are more than the sum of their parts: single-cell behavior has a complex relation to collective community behavior, in a manner perhaps cognate to the complex relation between atomic physics and condensed matter physics. Biofilm microbiology is a relatively young field by biology standards, but it has already attracted intense attention from physicists. Sometimes, this attention takes the form of seeing biofilms as inspiration for new physics. In this roadmap, we highlight the work of those who have taken the opposite strategy: we highlight the work of physicists and physical scientists who use physics to engage fundamental concepts in bacterial biofilm microbiology, including adhesion, sensing, motility, signaling, memory, energy flow, community formation and cooperativity. These contributions are juxtaposed with microbiologists who have made recent important discoveries on bacterial biofilms using state-of-the-art physical methods. The contributions to this roadmap exemplify how well physics and biology can be combined to achieve a new synthesis, rather than just a division of labor.